Implementasi Program Pendidikan Inklusi di Sekolah Alam Banyu Belik Kedung Banteng - Kuntari, Dhien; Raihan, Muhammad; Lutfiah, Tsalysatul; Khasanah, Uswatun (J-PGMI: Jurnal Pendidikan Guru MI, 2025)
Inclusive education is an educational system that accommodates all students, including children with special needs, to learn together in one learning environment. This concept is in line with the Indonesian national education philosophy that upholds access to education without discrimination. The implementation of inclusive education in Indonesia is based on government regulations, such as the Ministerial Decree No. 70 of 2009 and Law No. 20 of 2003 Article 32. Banyu Belik Nature School implements the concept of inclusive education by integrating the 2013 curriculum, the independent curriculum, and the adaptive curriculum called the "cassava curriculum". This program involves nature as the main learning medium and source, as well as develops life skills with an environmental awareness. However, there are several challenges in its implementation, such as the readiness of human resources, supporting facilities and infrastructure, public acceptance and attitudes, and policies that are not yet fully supportive. Efforts that can be made to overcome these challenges include training and mentoring for teachers, procurement of accessible facilities, public outreach, policy advocacy, and the establishment of a disability service unit. The success of inclusive education heavily depends on teacher competencies, collaboration among stakeholders, and a comprehensive transformation within the education system.